Sosialisasi Pemanfaatan Teknologi Digital Marketing untuk Meningkatkan Pendapatan UMKM - Uci Dwi Cahya; Muttaqin Muttaqin; Hendra Susanto (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The information of technology is important role as a solution to overcome problems in the field of product marketing. The presence of technology as a means of digital marketing today is helping people's needs, how much activity is spent using digital technology to fulfill their daily needs. The participants are required to be able to adjust to the conditions and developments of current transactions. The aim of this PKM program is to socialize technology as a means of product promotion so that the participants in PondokKemuningKecamatanLangsa Lama can increase the number of sales through digital marketing, and participants can adapt to new habits, namely digital marketing. The method used in this PKM uses 3 stages, namely the planning stage, the discussion stage, and the implementation stage. The results of the PKM activities regarding digital marketing socialization to participants in PondokKemuning, KecamatanLangsa Lama, it can be seen from the participants actors who were very enthusiastic about the presentation of digital marketing materials and training. This activity has a positive impact on participans actors, to increase the knowledge and understanding of participant actors about digital product marketing and increase confidence in marketing their products online.